Development of a new borehole probe for thermal conductivity scanning. (May 2017) - Sauer, David; Wagner, Steffen; Amro, Moh'd; Popov, Yuri; Rose, Frederick; Schramm, Andreas; Börner, Erik; Wünsch, Toni; Redondo-Robles, Héctor; Hesse, Gerold; Pfeiffer, Johannes
Highlights: A measuring system for in situ thermal conductivity scanning was developed. The probe measures in open hole areas and is based on optical scanning-technology. It allows fast high resolution measurements even in liquid filled boreholes. Abstract: Knowledge about the thermal conductivity of rock is essential for accurate design of geothermal plants. Thermal conductivity can be measured in situ, with low precision and coarse spatial resolution, or in a laboratory, where samples are subject to altered conditions and represent only limited sections of the borehole. We have developed and evaluated a new technology involving fast, high-resolution, and high-precision scanning of in-situ thermal conductivity within boreholes. The prototype demonstrated the feasibility of the technology for shallow geothermic wells, with an accuracy of 10%.